PERSEPSI MAHASISWA MENGGUNAKAN FASILITAS WI-FI DALAM MENCARI INFORMASI DI KALANGAN MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - ", Nawawi; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Their wi-fi facilities provided by the faculty, not infrequently of students gathered in front of the dean. Many students spend time to enjoy the facilities that are provided interrupted the completion of lecture hours. However, theis facility drawn some criticism or feedback from students on the wi-fi facility. This study aims to determine students perception of using the wi-fi in the search for information among the students of the faculty of social sciences and political science university of Riau and factors-factors that affect the perception of students take advantage of the wi-fi in search of information among students of faculty of social sciences and political science university in Riau The study used a qualitative descriptive method of data collection techniques of observation, interviews, and documentansi. The data obtained are then processed to be reduced, resulting conclusions are presented to the public. Informants in the study ware 12 based accidental sampling method that researchers use. As for the examination of the validity of the data the researcher used the extension of participation and triangulation techniques. The results of this study show that the perception of students take advantage of the wifi in search of information among students of facultyu of social sciences and political science university Riau sensation in this case the wifi speed is suffcient, attention in this respect can be seen from the access speed wifi and wifi hotspots it self, and interpretations whic students were quite happy to use wifi, wifi network due to slower and less stable..  Factors-factors that affect the perception of students take advantage of the wi-fi in the search for information among the students of the faculty of social sciences and political science university Riau,their taste experience in this facility provided less than satisfactory, the motivation in this case can save on the cost of the budget to buy an internet card and personality in this facility which is provided quite helpful and helped students.